2008
DOI: 10.1029/2007pa001517
|View full text |Cite
|
Sign up to set email alerts
|

Late Albian paleoceanography of the western subtropical North Atlantic

Abstract: [1] A late Albian-early Cenomanian record ($103.3 to 99.0 Ma), including organic-rich deposits and a d 13 C increase associated with oceanic anoxic event 1d (OAE 1d), is described from Ocean Drilling Program sites 1050 and 1052 in the subtropical Atlantic. Foraminifera are well preserved at these sites. Paleotemperatures estimated from benthic d 18 O values average $14°C for middle bathyal Site 1050 and $17°C for upper bathyal Site 1052, whereas surface temperatures are estimated to have ranged from 26°C to 31… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
63
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 55 publications
5
63
0
Order By: Relevance
“…The lithology of Hole 1050C changes from claystone below to chalk above the A/C boundary. A coring gap at 556.6-558.0 mbsf (Core 25/26), in which an unconformity is present, translates to a sedimentation gap of ,0.8 Myr based on the graphic correlation with shallower Site 1052 (Petrizzo and Huber 2006;Petrizzo et al 2008). It explains the limited occurrence of the OAE 1d black shales at this site as compared to Site 1052 (Wilson and Norris 2001;Petrizzo et al 2008).…”
Section: Methodsmentioning
confidence: 86%
See 4 more Smart Citations
“…The lithology of Hole 1050C changes from claystone below to chalk above the A/C boundary. A coring gap at 556.6-558.0 mbsf (Core 25/26), in which an unconformity is present, translates to a sedimentation gap of ,0.8 Myr based on the graphic correlation with shallower Site 1052 (Petrizzo and Huber 2006;Petrizzo et al 2008). It explains the limited occurrence of the OAE 1d black shales at this site as compared to Site 1052 (Wilson and Norris 2001;Petrizzo et al 2008).…”
Section: Methodsmentioning
confidence: 86%
“…Systematic A-C paleoceanographic studies carried out at North Atlantic ODP Sites 1050 and 1052 of the Blake Nose depth transect ( Fig. 1) (Wilson and Norris 2001;Watkins et al 2005;Petrizzo et al 2008) and Deep Sea Drilling Project (DSDP) Site 547 off Morocco (Nederbragt et al 2001) have revealed that stratigraphic distribution of planktonic foraminifera in both regions and of nannofossils in the eastern North Atlantic are consistent with the global compilation by Leckie et al (2002). In the western North Atlantic, on the other hand, nannoplankton at the time of OAE 1d suffered local extinctions of 20% of taxa (biased to deep-dwelling representatives), preceded by a long-term increase in high-fertility indicative taxa, suggesting regional upwelling and/or deep mixing (Watkins et al 2005).…”
Section: Paleoceanographic Backgroundmentioning
confidence: 99%
See 3 more Smart Citations